The role of the reader : - Eco, Umberto (Indiana University Press, 1979)
This collection of nine essays focuses on the role of the reader in textual interpretation. The essays propose a dialectic between "open" and "closed" texts, between a work of art that actively involves the reader in its production and one that holds the reader at bay and seeks to evoke a limited and predetermained response.